1999
DOI: 10.1034/j.1399-0020.1999.280606.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of nonsurgical management of condylar fractures in children

Abstract: Twenty-five patients with 28 condylar or subcondylar fractures, sustained during their growth period and treated nonsurgically, have been followed for an average period of 15 years. The fractures were classified as intracapsular, high condylar neck and low condylar neck fractures. In 5 patients, two weeks of intermaxillary fixation, followed by elastic traction in order to achieve a proper occlusion, was applied. All the other patients were treated by instruction, exercises and observation. In 4 patients, subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…The higher incidence of condylar fractures in children may be explained by the higher proportion of medullary bone with only a thin rim of cortex. Nonsurgical management of condylar fractures of the mandible in children is still the method of choice [10]. Para-symphyseal fractures at 19.14 % were the second most common site in our series.…”
Section: Discussionmentioning
confidence: 67%
“…The higher incidence of condylar fractures in children may be explained by the higher proportion of medullary bone with only a thin rim of cortex. Nonsurgical management of condylar fractures of the mandible in children is still the method of choice [10]. Para-symphyseal fractures at 19.14 % were the second most common site in our series.…”
Section: Discussionmentioning
confidence: 67%
“…With the exception of undisplaced, intracapsular fractures and fractures in pediatric patients younger than 12 years of age [14][15], most mandibular condylar fractures should be treated with open reduction and rigid fixation. Points to be clarified regarding surgical treatment, is how many fixation devices should be used [6], and the choice of approach for treating condylar fractures.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have suggested that the treatment of condylar fractures by open reduction and rigid fixation offers much better anatomic results [6][7][8][9][10][11][12][13]. Conservative treatment is still the choice of treatment for intracapsular or comminuted fractures and fractures in pediatric patients [14,15]. Though closed reduction is a simple and easy method of treatment of condylar fractures but long-term complications like pain, arthritis, open bite, inadequate restoration of vertical height of the ramus leading to malocclusion and ankylosis do exist with closed reduction method [16].…”
Section: Introductionmentioning
confidence: 99%
“…It concluded that non-surgical treatment of condylar fractures in children was still the method of choice. 5 This particular case is unusual in that the trauma caused an intracapsular vertical split fracture of the condyle head. Interestingly a retrospective study of paediatric condylar fractures in Finland found that intracapsular fractures were more common in 6-year-olds and under than any other type of condylar fracture.…”
Section: Commentmentioning
confidence: 99%